Non-melanoma skin tumors: a retrospective study of the epidemiological profile and outcome from compromised margins - Guilherme Augusto Bachtold; Carolina da Silveira Welter; Carolina Martendal Cerrutti; Djulia Adriani Frainer; Heloiza Fiamoncini; Roberta Penteado (Revista Brasileira de Cirurgia Plástica, 2022)
Introduction: Non-melanoma skin neoplasms are responsible for 30% of all malignant tumors in Brazil. The main objective of this article was to evaluate the epidemiological profile and the approach taken from the histopathological diagnosis of compromised margins in patients with non-melanoma skin neoplasms treated primarily with surgery. Methods: This is an observational retrospective cohort. Data were collected from electronic medical records of 1495 patients, resulting in 2457 non-melanoma skin neoplasms, from January 2015 to December 2019. Results: There was a higher prevalence in men (52.4%) and between the sixth and seventh decades of life (41.4%). Basal cell carcinoma was the most common histological type (75%). Those over the age of 61 are 57.2% more likely to develop basal cell carcinoma (relative risk=1,572 (95% CI: 1,316-1,878; p<0. 0001). Compromised margins were reported in 15.8% of cases, being more common on the face (19.5%) and in patients with basal cell carcinoma (p<0.05), with relative risk=1,382 (95%CI: 1,135-1,683; p=0.0013). Additional treatment was indicated in 74.6% of cases, with the most common approaches being margin expansion (55.6%) and radiotherapy (42.4%). The choice between intervention or observation was related to the histological type (p<0.05), but it was not possible to affirm its relationship with the age group (p>0.05). Conclusion: The study allowed a better understanding of the profile of patients with non-melanoma skin neoplasms and the percentage of compromised margins after initial surgical excision and the treatment performed.